The metabolic and neuroinflammatory changes induced by consuming a cafeteria diet are age-dependent. (3rd April 2019) - Teixeira, Deborah; Cecconello, Ana Lucia; Partata, Wania Aparecida; de Fraga, Luciano Stürmer; Ribeiro, Maria Flávia Marques; Guedes, Renata Padilha
Abstract : Objectives: To compare the effects of a palatable cafeteria diet on serum parameters and neuroinflammatory markers of young and aged female Wistar rats. Methods: Three-month-old (young) and 18-month-old (aged) female Wistar rats had access to a cafeteria diet (Caf-Young, Caf-Aged) or a standard chow diet (Std-Young, Std-Aged). Results: The Caf-Young group showed a higher food consumption, weight gain, visceral fat depot, serum insulin and leptin levels, and the insulin resistance index (HOMA-IR) than the Std-Young group. The Caf-Aged group exhibited an increase in interleukin-1 levels in the cerebral cortex and hippocampus. The number of GFAP-positive cells did not differ between the groups, but there was a diet effect in the cerebral cortex and an age effect in the hippocampus. Phospho-tau expression did not differ between the groups. Discussion: The 3- and 18-month-old rats responded differently to a cafeteria diet. Insulin and leptin levels are elevated in young animals fed a cafeteria diet, whereas aged animals are prone to neuroinflammation (indicated by an increase in interleukin-1β levels). A combination of hypercaloric diet and senescence have detrimental effects on the inflammatory response in the brain, which may predispose to neurological diseases.